Pemeriksaan Tekanan Darah dan Konseling Tentang Hipertensi di Desa Lowungu, Bejen - Mega Pristyo, Nasabila; Novi Kurniasari, Erlinda; Navik Velayati, Rizqa; Avriella Khasanda, Pyrena; Fikriyah, Bayyanatul; Dwi Safitri, Alfina; Galang Saputra, Moh. Fitrah; Eric Junico, Lian; Nindyo Sumarno, Radiktyo (PADMA, 2024)
Although hypertension is a worldwide public health problem, healthcare providers still do not place the disease at the top of the priority scale. The negative effects of this disease, such as stroke and coronary heart disease, should not be ignored. In Lowungu Village, Temanggung Regency, there are several people suffering from hypertension, with a percentage of 36% who have several complications. Counseling on hypertension, including blood pressure checks, is necessary due to the high incidence rate and risk of hypertension complications. This community service activity aims to provide Lowungu villagers with the ability to monitor their health conditions. Counseling on hypertension and health checks are part of the procedure of this activity. Participants must register before the counseling begins. This counseling gives participants a better understanding of hypertension and they can use herbal plants growing around the house to prevent or treat hypertension